Teatro pedagógico: performance cultural através da moda e a relação de construção identitária mediada pela mídia massiva - Santos, Elenice Nogueira (2016)
This research aims to recognize the place and cultural identity of adolescents at school. The starting point has the culture as a continuous process in constant transformation that involves the community and its surrounding in general. The Fashion and Media, considered as cultural vectors, promote meaning to manifestations of the age group in question, accompanied by technological advances, access to information and industrial production. The actual school as a formative unit with pedagogical thoughts teaches that the classroom practices are linked to the historical, social and cultural environment. Therefore, the cultural event constitutes a part of the world of the subject. At this point, you can link 'performance, space and identity' to the term "Theater", which is the start and final point for proposals that allow critical-reflexive actions to be developed in the school curriculum. Considering the common needs and desires of students from Grade 6 the Municipal School Edgar Torres on Toritama-PE, it was attempted to understand the critical-aesthetic relationship before the tensions between aspects of development of the students included in the educational proposals through the theatrical practices.